2021
DOI: 10.3390/pathogens11010005
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Sensing and Assimilation by the Fungal Pathogen Candida albicans in the Human Host

Abstract: Nutrient uptake is essential for cellular life and the capacity to perceive extracellular nutrients is critical for coordinating their uptake and metabolism. Commensal fungal pathogens, e.g., Candida albicans, have evolved in close association with human hosts and are well-adapted to using diverse nutrients found in discrete host niches. Human cells that cannot synthesize all amino acids require the uptake of the “essential amino acids” to remain viable. Consistently, high levels of amino acids circulate in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 138 publications
1
21
0
Order By: Relevance
“…2D). In the absence of glucose, we found that the expression of cytoplasmic Gdh2 (8) , one of the key enzymes in central nitrogen metabolism, is partly regulated by Put3 (Fig. 2D).…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…2D). In the absence of glucose, we found that the expression of cytoplasmic Gdh2 (8) , one of the key enzymes in central nitrogen metabolism, is partly regulated by Put3 (Fig. 2D).…”
Section: Discussionmentioning
confidence: 94%
“…In C. albicans , as in S. cerevisiae , proline catabolism is induced by the presence of proline and due to being mitochondrial localized is sensitive to glucose repression (reviewed in ( 8 )) (Fig. 2A).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations